Establishment and characterization of a multi-drug resistant cell line for canine mammary tumors - Zhou, Chaoyu; Lin, Zixiang; Li, Xinqiu; Zhang, Di; Song, Peijia (Frontiers in Veterinary Science, 2023)
Canine mammary tumors are the most common tumor disease of female dogs, and adjuvant chemotherapy often results in multi-drug resistance. Currently, the mechanisms underlying the development of tumor multi-drug resistance are unclear. The translation of research applications that can be used to effectively overcome tumor resistance is similarly hampered. Therefore, it is urgent to construct multi-drug resistance models of canine mammary tumors that can be used for research, to explore the mechanisms and means of overcoming resistance. After more than 50 consecutive generations, we found that the morphology of the resistant cell lines tended to be mesenchymal-like and heterogeneous under light microscopy compared to the parental cell lines, developing resistance to doxorubicin and other commonly used chemotherapeutic drugs. The transcript and protein expression levels of BCRP were higher in the resistant cell lines, while there was no significant difference in P-glycoprotein. Secondly, the migration and invasion ability of the resistant cell lines were significantly elevated compared to the parental cell lines, and the expression of E-cadherin was decreased and the expression of vimentin and mucin 1-N terminus was increased. In summary, the canine mammary tumor cell line CMT-7364/R, constructed by high-dose drug pulse method, was multi-drug resistant. Compared to its parental cell line, CMT-7364/R has decreased growth rate, overexpression of BCRP and increased migration and invasion ability due to EMT. The results of this study showed that CMT-7364/R might serve as a model for future studies on tumor drug resistance.